AKTIVITAS OSMOREGULASI IKAN CAPUNGAN TITIK HITAM (Sphaeramia orbicularis) PADA LINGKUNGAN BERSALINITAS - Samsu Adi Rahman; Frederik Dony Sangkia; Iksan Randa Manuli; Muhammad Safir (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2024)
Osmoregulation in fish is a process that involves regulating the balance of water and electrolytes in their bodies, especially changes in salinity in the water environment where they live. This study aims to determine the osmoregulatory ability of orbiculate cardinalfish (Sphaeramia orbicularis) to changes in salinity. This research used a Completely Randomized Design (CRD) with four treatments, namely control (no treatment), 150 mL fresh water/L sea water, 100 mL fresh water/L sea water, and 50 mL fresh water/L sea water and respectively three repetitions each. orbiculate cardinalfish with a length ranging from 5.2 ± 0.46 cm and a weight of 2.3 ± 0.25 g were kept in each rearing container and given treatment based on each treatment. The parameters observed in this study were the fish's osmoregulatory ability by looking at fish behavior, external organs (fish skin and gills), and examination of internal organs (kidneys), and survival rate. The results showed that the control treatment at the end of the study had abnormal kidney and gill conditions. Meanwhile, the dilution treatment of 150 mL fresh water/L sea water, 100 mL fresh water/L sea water, and 50 mL fresh water/L sea water showed normal conditions or symptoms in the kidneys and gills, but the fish skin organs showed pale or faded in all treatments. Based on these results it can be concluded that the best treatment is 150 mL fresh water/L sea water treatment.